Knee arthroscopy postoperative analgesia by multimodal cocktail regime - Madan Mohan Ballal; Pavan Kumar Chebbi; Prabhu Vasudev; Sathish Kumar S; Dharmesh Chikkegowda (International Journal of Medical Research and Review, 2016)
Background: Post-operative knee pain management have become a challenge to provide early relief and pain free postoperative care to the patient. Adequate analgesia influences the early rehabilitation of the patient and hospital stay.Many factors have been implicated to influence post arthroscopy pain such anesthetic technique, residual effects of perioperative analgesia, patient pain threshold, preoperative pain level, the use and duration of tourniquet exsanguination, surgical trauma involved, volume of drug injected, the experience of the surgeons, the sex of the patient and the postoperative activity level of the patients.The purpose of this study is to assess the efficacy of the multidrug regime for management of postoperative pain during first 24 hours.Methods: In our study 57 patients of both the sexes were evaluated for postoperative pain following various elective arthroscopic knee surgeries such as ligament reconstruction, cartilage procedures and diagnostic arthroscopic procedures. Patients were evaluated for pain using visual analogue score at 6th hour,12th hour and 24 hours’ post-operative. A cocktail prepared of multidrug was used for the study.Results: The new cocktail regime provides adequate analgesia with no patients requiring additional analgesia for first 12 hours and only 2 patients whose VAS [visual analogue scale] was greater than 4 required additional analgesia at the end of 24 hours postoperative.Conclusion: Multi drug cocktail regime provides a good analgesic for post-operative knee arthroscopic surgery without the need of rescue analgesics. Intra articular local analgesia reduces overall use of parenteral analgesics and also helps in quicker rehabilitation.